Red-mud-based aggregate, red-mud-based water permeable brick and preparation method of red-mud-based aggregate

By using lightly burned dolomite, mineral powder and fly ash in the preparation of red mud, reacting with red mud, ettringite and gel products are generated, and the mineral phase composition of red mud is changed, the problem of harmful heavy metal leaching in red mud is solved, and the high compressive strength and environmentally friendly red mud-based aggregate is achieved.

CN119822780APending Publication Date: 2025-04-15FOSHAN DONGPENG CERAMIC +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510017669.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing technology for preparing aggregates for red mud has problems with harmful heavy metal leaching, resulting in safety hazards and environmental pollution.

Method used

Lightly burned dolomite, mineral powder and fly ash react with the hydroxide in the red mud to produce ettringite, calcium silicate hydrate and calcium aluminate hydrate products, changing the mineral phase composition of the red mud, forming a dense matrix structure, and preventing the leaching of harmful heavy metals.

Benefits of technology

Effectively prevent the leaching of harmful heavy metals in red mud, enhance the compressive strength of red mud-based aggregates, realize large-scale recycling and utilization of red mud, and reduce environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005230369690000111
    Figure BDA0005230369690000111
  • Figure BDA0005230369690000121
    Figure BDA0005230369690000121
  • Figure BDA0005230369690000131
    Figure BDA0005230369690000131
Patent Text Reader

Abstract

The invention discloses a red-mud-based aggregate, a red-mud-based water permeable brick and a preparation method thereof.The preparation method of the red-mud-based aggregate comprises the following steps that S11, light-burned dolomite, mineral powder, fly ash, red mud and water are evenly mixed, ball-milled and dried, and then a matrix is prepared; s12, uniformly mixing silicon powder, magnesium silicate cement and modified water glass to prepare neat paste A; and S13, spraying water to wet the matrix, pouring the matrix into the neat paste A, uniformly stirring to form a hard shell on the surface of the matrix by the neat paste A, and curing the hard shell to obtain the red mud-based aggregate. According to the invention, light-burned dolomite, mineral powder and fly ash are adopted as raw materials to generate ettringite, gelling calcium silicate hydrate, calcium aluminate hydrate and other products with red mud, so that the mineral phase composition of the red mud is changed. The ettringite and the gel product grow in a staggered mode, a compact matrix structure is formed, the porosity of a matrix is reduced, and leaching of harmful heavy metal in the red mud is effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of red mud, in particular to red mud-based aggregate, red mud-based permeable bricks and preparation methods thereof. Background Art

[0002] In the production process of the alumina industry, red mud, as a major solid waste, is produced in large quantities and continues to accumulate, which has become an extremely difficult environmental problem. The chemical composition of red mud is complex and diverse, and it contains a considerable amount of alkaline substances, such as strong alkaline components such as sodium hydroxide and calcium hydroxide, as well as harmful heavy metal elements such as radium, potassium, and thorium. These special components give red mud significant environmental hazards.

[0003] In recent years, in order to explore ways to recycle red mud, the use of red mud to prepare aggregates has become one of the research hotspots. However, in actual application, it was found that the existing technology for preparing aggregates from red mud is not perfect. Due to the characteristics of red mud itself and possible process defects in the aggregate preparation process, the prepared aggregates often have the problem of leaching of harmful heavy metals. The leaching of such harmful heavy metals, whether in the production, transportation, and storage of aggregates, or in their subsequent use as building materials in construction projects, road projects and other scenarios, poses certain safety hazards. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing red mud-based aggregate, using light-burned dolomite, mineral powder and fly ash as raw materials and hydroxide in red mud to generate products such as ettringite, gelled calcium silicate hydrate and calcium aluminate hydrate products (i.e. CSH gel and CAH gel), thereby changing the mineral phase composition of red mud. The ettringite and the gel product grow alternately to form a dense matrix structure, reduce the porosity of the matrix, and effectively prevent the leaching of harmful heavy metals in red mud.

[0005] The purpose of the present invention is to provide a red mud-based aggregate. Through the above-mentioned red mud-based aggregate preparation method, the red mud raw material can be recycled on a large scale to form a red mud-based aggregate with high compressive strength and harmful heavy metals that are not easy to leach out, thereby solving the problem of heavy metal leaching in the traditional red mud recycling process.

[0006] The object of the present invention is to provide a method for preparing red mud-based permeable bricks. The modified water glass can provide an alkaline environment for step S21 to activate the silicate and aluminate components in the red mud. The activated silicate and aluminate components can react more fully with substances such as calcium hydroxide in the system to generate more gelling products such as CSH gel and C(N)-ASH gel, thereby changing the mineral phase composition of the red mud and solving the problem of heavy metal leaching in the traditional red mud recycling process.

[0007] A red mud-based permeable brick is prepared by a red mud-based aggregate preparation method to make red mud into a red mud-based permeable brick, thereby achieving effective resource utilization of red mud and converting the originally waste and harmful substances into valuable building materials.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] A red mud-based aggregate comprises the following steps:

[0010] S11, mixing light-burned dolomite, mineral powder, fly ash, red mud and water uniformly, ball-milling and drying to obtain a matrix;

[0011] S12, uniformly mixing silica fume, magnesium silicate cement and modified water glass to prepare a pure slurry A;

[0012] S13, spraying water to wet the substrate, pouring the substrate into the slurry A, stirring evenly, the slurry A forms a hard shell on the surface of the substrate, and obtaining red mud-based aggregate after the hard shell is solidified.

[0013] Furthermore, in the S11, 2-5 parts of light-burned dolomite, 2-5 parts of mineral powder, 2-5 parts of fly ash, 10-15 parts of red mud and 1-3 parts of water are added in sequence by weight, mixed evenly, and after mixing, ball-milled at a pressure of 5-6 MPa to form the matrix.

[0014] Furthermore, in S12, 20-50 parts of silica powder, 20-50 parts of magnesium silicate cement and 5-15 parts of modified water glass are added in sequence by weight and mixed evenly to form the slurry A.

[0015] Further, the modified water glass comprises 5-15 parts of water glass, 1-2 parts of NaOH powder and 20-30 parts of water;

[0016] In S12, 1-2 parts of NaOH powder and 20-30 parts of water are added in sequence by weight, and after mixing evenly, 5-15 parts of water glass are added and mixed thoroughly to form the modified water glass;

[0017] The modulus of the modified water glass is 1.3-1.7.

[0018] Furthermore, the water-to-binder ratio of the pure slurry A is 0.40-0.55.

[0019] Furthermore, the particle size of the matrix is ​​1-10 mm, and the thickness of the net slurry A of the red mud-based aggregate is 0.90-1.2 mm.

[0020] A red mud-based aggregate, characterized in that it is prepared by a preparation method of the red mud-based aggregate.

[0021] A method for preparing red mud-based permeable bricks, using the red mud-based aggregate according to claim 7, comprises the following steps:

[0022] S21, mixing the mineral powder, fly ash, red mud and modified water glass uniformly to form a pure slurry B;

[0023] S22, mixing the red mud-based aggregate and the pure slurry B to prepare red mud-based permeable bricks.

[0024] Furthermore, in S21, 20-50 parts of mineral powder, 10-15 parts of fly ash, 10-20 parts of red mud and 5-15 parts of modified water glass are added in sequence by weight, and mixed evenly to form a pure slurry B;

[0025] The water-to-binder ratio of the pure slurry B is 0.28-0.38.

[0026] A red mud-based permeable brick, characterized in that it is prepared by the preparation method of the red mud-based aggregate.

[0027] Compared with the prior art, the technical solution proposed in the present invention can have the following beneficial effects:

[0028] 1. Using light-burned dolomite, mineral powder and fly ash as raw materials and the hydroxide in red mud, ettringite, gelled calcium silicate hydrate and calcium aluminate hydrate products (i.e. CSH gel and CAH gel) are generated, thereby changing the mineral phase composition of red mud. The ettringite and gel products grow alternately to form a dense matrix structure, reduce the porosity of the matrix, and effectively prevent the leaching of harmful heavy metals in red mud;

[0029] 2. The pure paste A after uniformly mixing silica fume, magnesium silicate cement and modified water glass can tightly wrap the matrix, so that a hard shell is formed on the surface of the matrix. The hard shell is one or more layers of geopolymer. The dense hard shell structure can not only further prevent the leaching of harmful heavy metals in red mud, but also enhance the compressive strength of red mud-based aggregates. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further explained below in conjunction with specific implementation methods.

[0031] The invention provides red mud-based aggregate, red mud-based permeable brick and a preparation method thereof.

[0032] A method for preparing red mud-based aggregate comprises the following steps:

[0033] S11, mixing light-burned dolomite, mineral powder, fly ash, red mud and water uniformly, ball-milling and drying to obtain a matrix;

[0034] S12, uniformly mixing silica fume, magnesium silicate cement and modified water glass to prepare a pure slurry A;

[0035] S13, spraying water to wet the substrate, pouring the substrate into the slurry A, stirring evenly, the slurry A forms a hard shell on the surface of the substrate, and obtaining red mud-based aggregate after the hard shell is solidified.

[0036] At present, a large amount of red mud is produced every year in the world. Due to the huge amount of red mud stockpiles and the difficulty of natural degradation and elimination of alkaline substances and harmful heavy metal elements in it, the soil, water and atmospheric environment around many red mud dumps have been polluted to varying degrees.

[0037] Therefore, in this scheme, lightly burned dolomite, mineral powder and fly ash are used as raw materials to react with the hydroxide in red mud to generate products such as ettringite, gelled calcium silicate hydrate and calcium aluminate hydrate products (i.e. CSH gel and CAH gel), thereby changing the mineral phase composition of red mud. The ettringite and gel products grow alternately to form a dense matrix structure, reduce the porosity of the matrix, and effectively prevent the leaching of harmful heavy metals in red mud.

[0038] The pure paste A after uniformly mixing silica fume, magnesium silicate cement and modified water glass can tightly wrap the matrix, so that a hard shell is formed on the surface of the matrix. The hard shell is one or more layers of geopolymer, and the dense hard shell structure can not only further prevent the leaching of harmful heavy metals in red mud, but also enhance the compressive strength of red mud-based aggregate.

[0039] In addition, before the pure slurry A wraps the substrate, the substrate needs to be dried first, which can effectively avoid the cracking problem caused by the difference in humidity inside and outside the red mud-based aggregate. Then, the surface of the substrate is sprayed with wet water to improve the toughness of the outer layer of the substrate, so that the pure slurry A can wrap the surface of the substrate more tightly, thereby forming a hard shell, which solves the problem of harmful heavy metal leaching after traditional red mud is prepared into aggregate.

[0040] In the S11, 2-5 parts of light-burned dolomite, 2-5 parts of mineral powder, 2-5 parts of fly ash, 10-15 parts of red mud and 1-3 parts of water are added in sequence by weight, mixed evenly, and after mixing, ball-milled at a pressure of 5-6 MPa to form the matrix.

[0041] Light-burned dolomite, mineral powder and fly ash can react with active ingredients in red mud such as alumina (Al2O3) and silicon dioxide (SiO2) to generate products such as CSH gel and C(N)-ASH gel, which not only changes the mineral phase composition of red mud, but also enhances the compressive strength and durability of red mud-based aggregates.

[0042] Specifically, when CaO in light-burned dolomite first reacts with water to generate Ca(OH)2, Ca(OH)2 will not only further react with SiO2 in red mud to form an amorphous calcium silicate hydrate, namely CSH gel. The reaction formula is as follows:

[0043] CaO+SiO2+H2O→CSH gel

[0044] Ca(OH)2 will also react with CaAl2O4 in red mud to promote the formation of ettringite. The reaction formula is as follows:

[0045] 3CaO·Al2O3+3(Ca2SO4·2H2O)→Ca6Al2(SO4)3(OH) 12 ·26H2O

[0046] In addition, both mineral powder and fly ash contain a certain amount of active oxides and sulfates. In an alkaline environment, these active oxides will first react with Ca(OH)2 to form gel products such as CSH gel and CAH gel. Among them, calcium aluminate hydrate will further react with sulfate ions in red mud to form calcium aluminate. The reaction formula is as follows:

[0047] Al2O3+Ca(OH)2+H2O→CAH gel

[0048] 3C-A-H+Ca2SO4·2H2O+26H2O→Ca6Al2(SO4)3(OH) 12 ·26H2O

[0049] It is worth noting that in S11, a roller ball forming machine or a disc ball forming machine can be used to prepare a matrix with a particle size within a predetermined range. Specifically, under a molding pressure of 5-6MPa, the rotation speed of the roller ball forming machine is 15rpm, and the rotation speed of the disc ball forming machine is 16rpm. The above parameter settings can ensure that the matrix can achieve sufficient density and mechanical strength, and reduce the leaching of harmful heavy metals.

[0050] In the S12, 20-50 parts of silica powder, 20-50 parts of magnesium silicate cement and 5-15 parts of modified water glass are added in sequence by weight, and mixed evenly to form the slurry A.

[0051] It should be noted that silica powder and magnesium silicate cement should be added in sequence, and after the silica powder and magnesium silicate cement are evenly stirred, the modified water glass should be slowly added after they are fully reacted, and stirring should be continued to ensure that each material can be evenly dispersed.

[0052] Among them, magnesium silicate cement itself has good gelling properties, and it will form a stable gel structure during the hydration process to bond various raw materials together. Among them, the silica powder and magnesium silicate cement are evenly mixed, so that the silica powder can be filled in the gaps between the magnesium silicate cement particles, playing a micro-filling effect, thereby enhancing the compressive strength of red mud-based aggregates.

[0053] Moreover, the active SiO2 component in the silica fume can also react with Ca(OH)2 in the cement hydration product to produce a volcanic ash reaction, further generating CSH gel, which enhances the overall strength performance of the paste A and makes it more able to withstand external loads. Therefore, the paste A forms a multi-layer geopolymer on the surface of the matrix, and the geopolymer forms a hard shell after solidification. The dense hard shell structure can not only further prevent the leaching of harmful heavy metals, but also improve the compressive and flexural strength indicators of the red mud-based aggregate.

[0054] The modified water glass comprises 5-15 parts of water glass, 1-2 parts of NaOH powder and 20-30 parts of water;

[0055] In S12, 1-2 parts of NaOH powder and 20-30 parts of water are added in sequence by weight, and after mixing evenly, 5-15 parts of water glass are added and mixed thoroughly to form the modified water glass;

[0056] The modulus of the modified water glass is 1.3-1.7.

[0057] Among them, the modified water glass contains a large amount of alkaline components such as SiO2 and Na2O, which can provide an alkaline environment, activate and accelerate the hydration reaction of silica powder and silicate cement in step S12, promote the hydration reaction between CaO, SiO2 and H2O, and accelerate the formation of products such as CSH gel and C(N)-ASH gel.

[0058] It should be noted that in this scheme, the modulus of the modified water glass is controlled within a predetermined range, which can balance the alkali activity of the modified water glass. Too low a modulus will lead to an excessively high alkali content in the cementitious material, which may affect the subsequent red mud-based aggregate strength indicators such as compression and flexural strength; while too high a modulus will reduce the reactivity of the modified water glass, and fail to fully stimulate the hydration reaction of the red mud, resulting in the leaching of harmful heavy metals.

[0059] In addition, this scheme also has restrictions on the order of adding modified water glass. If NaOH powder is in direct contact with water glass, it may cause uneven reaction or excessive local concentration of modified water glass, affecting the performance of subsequent pure slurry A. Therefore, in preparing modified water glass, first stir NaOH powder and water thoroughly, and then add water glass to ensure that NaOH powder can fully react with water glass.

[0060] The water-to-binder ratio of the pure slurry A is 0.40-0.55.

[0061] The water-cement ratio is controlled within a predetermined range, so that silica fume, magnesium silicate cement and modified water glass can move relatively freely in the slurry and can be better mixed with each other, effectively ensuring that the net slurry A has good fluidity and high strength.

[0062] If the water-binder ratio of the paste A is too low, the water required for the hydration reaction is insufficient, the cementitious materials such as magnesium silicate cement cannot be fully hydrated, and the solidification time of the paste A on the substrate surface is accelerated, and it is impossible to ensure that a hard shell is formed on the substrate surface. If the water-binder ratio of the paste A is too high, the higher fluidity will reduce the density of the paste A, affecting the subsequent red mud-based aggregate in terms of strength indicators such as compression and flexural strength.

[0063] The particle size of the matrix is ​​1-10 mm, and the thickness of the net slurry A of the red mud-based aggregate is 0.90-1.2 mm.

[0064] The particle size of the matrix is ​​within the range of 1-10mm, and a variety of particles of different particle sizes can be matched to form a good particle gradation. Particles with larger particle sizes (such as 8-10mm) can play the role of skeleton support in the aggregate structure and bear greater loads; while particles with smaller particle sizes (such as 1-3mm) can fill the gaps between large particles to make the aggregate structure more compact. Matrix aggregates with a particle size of 1-10mm can provide higher performance at a lower cost in most applications, effectively control engineering costs, and improve the economic benefits of the project.

[0065] Within the thickness range of 0.90-1.2 mm, the balance between the concentration of reactants and the reaction conditions can be just maintained, so that the pure slurry A can orderly form one or more layers of geopolymers on and near the surface of the matrix. These geopolymers are intertwined and connected with each other, further enhancing the structural stability and performance of the red mud-based aggregate.

[0066] If the thickness of the pure paste A is too thick, the overall weight of the red mud-based aggregate may increase, and uneven internal stress may occur during the curing process, resulting in cracking of the hard shell and affecting the mechanical properties of the red mud-based aggregate.

[0067] A red mud-based aggregate is prepared by a method for preparing a red mud-based aggregate. By means of the method for preparing the red mud-based aggregate, the red mud raw material can be recycled on a large scale to form a red mud-based aggregate with high compressive strength and no harmful heavy metals being easily leached, which can replace ordinary building sand and be widely used in engineering applications such as construction.

[0068] A method for preparing red mud-based permeable bricks, using the red mud-based aggregate, comprises the following steps:

[0069] S21, mixing the mineral powder, fly ash, red mud and modified water glass uniformly to form a pure slurry B;

[0070] S22, mixing the red mud-based aggregate and the pure slurry B to prepare red mud-based permeable bricks.

[0071] Modified water glass can provide an alkaline environment for step S21, activate the silicate and aluminate components in the red mud, and the activated silicate and aluminate components can react more fully with substances such as calcium hydroxide in the system to generate more CSH gel, C(N)-ASH gel and other gelling products, thereby changing the mineral phase composition of the red mud and solving the problem of heavy metal leaching in the traditional red mud recycling process. The increase in the amount of gelling product generated helps to significantly improve the early and late strengths of the pure slurry B, so that the red mud-based permeable bricks can reach the use strength requirements faster and maintain good mechanical properties during long-term use.

[0072] Moreover, gelling products such as CSH gel and C(N)-ASH gel can effectively fill the pores of the pure slurry B, making the microstructure of the pure slurry B more compact, reducing the channels for the leaching of harmful heavy metals, reducing the potential harm of red mud-based permeable bricks to the environment, and improving the environmental safety of the product.

[0073] In S21, 20-50 parts of mineral powder, 10-15 parts of fly ash, 10-20 parts of red mud and 5-15 parts of modified water glass are added in sequence by weight, and mixed evenly to form a pure slurry B;

[0074] The water-to-binder ratio of the pure slurry B is 0.28-0.38.

[0075] It is worth noting that the three solid materials, namely, mineral powder, fly ash and red mud, should be added in batches in sequence to ensure uniformity during the stirring process and to avoid a certain material from reacting with water too early to produce agglomeration. Among them, the preparation method of modified water glass is consistent with step S12, and NaOH powder needs to be mixed with water first, and then water glass is added to ensure the uniformity of the modified water glass and prevent the modified water glass from being locally too thick or agglomerated.

[0076] Among them, when the water-cement ratio of the neat slurry B is lower than 0.28, the water content in the neat slurry B is too little to provide sufficient lubrication, making it difficult to mix the mineral powder, fly ash and red mud evenly, limiting the production of gelling products such as CSH gel and C(N)-ASH gel, and seriously affecting the performance of the neat slurry B.

[0077] Moreover, in step S22, when the pure slurry B is mixed with the red mud-based aggregate, due to the low fluidity of the pure slurry B, it is easy to cause the internal structure of the red mud-based permeable brick to be uneven, and the red mud-based permeable brick may be partially dense and partially loose.

[0078] When the water-cement ratio of neat paste B is higher than 0.38, a large amount of water occupies more space in neat paste B. During the drying or hardening process of neat paste B, more pores will be left after the water evaporates, making the structure of the red mud-based permeable brick loose and reducing its density. This not only reduces the mechanical strength of the red mud-based permeable brick, but also reduces the impermeability of the red mud-based permeable brick, resulting in the leaching of harmful heavy metals in the red mud.

[0079] A red mud-based permeable brick is prepared by the method for preparing a red mud-based aggregate.

[0080] The large amount of red mud accumulation has always been an environmental problem faced by the alumina industry. It contains alkaline substances and harmful heavy metal elements, which will cause pollution to soil, water bodies, etc. The red mud is made into red mud-based permeable bricks through the preparation method of red mud-based aggregate, which realizes the effective resource utilization of red mud, converts the originally waste and harmful substances into valuable building materials, greatly reduces the stockpile of red mud, and reduces the direct pollution risk of red mud to the environment.

[0081] The present invention is further described below in conjunction with embodiments and comparative examples.

[0082] Examples 1-3

[0083] The raw materials listed in Table 1 below were prepared accordingly, and the red mud-based aggregates and red mud-based permeable bricks of Examples 1-3 were prepared respectively according to the process parameters listed in Table 1 and the following steps.

[0084] S11, adding 2-5 parts of light-burned dolomite, 2-5 parts of mineral powder, 2-5 parts of fly ash, 10-15 parts of red mud and 1-3 parts of water in sequence by weight, mixing evenly, and after mixing, ball milling at a pressure of 5-6 MPa to form a matrix;

[0085] S12, add 1-2 parts of NaOH powder and 20-30 parts of water in sequence by weight, mix well, then add 5-15 parts of water glass, mix well to form modified water glass; add 20-50 parts of silica fume, 20-50 parts of magnesium silicate cement and 5-15 parts of modified water glass in sequence, mix well to form slurry A;

[0086] S13, spraying water to wet the substrate, pouring the substrate into the slurry A, the slurry A forms a hard shell on the surface of the substrate, and after the hard shell is solidified, a red mud-based aggregate is obtained;

[0087] S21, add 20-50 parts of mineral powder, 10-15 parts of fly ash, 10-15 parts of red mud, and 5-15 parts of modified water glass in order by weight, and mix well to form a pure slurry B;

[0088] S22, mixing red mud-based aggregate and pure paste B to prepare red mud-based permeable bricks.

[0089] Among them, the modulus of the modified water glass is 1.3-1.7; the water-binder ratio of the net slurry A is 0.40-0.55; the thickness of the net slurry A of the red mud-based aggregate is 0.9-1.2 mm; the water-binder ratio of the net slurry B is 0.28-0.38.

[0090] Table 1

[0091]

[0092] Comparative Example 1

[0093] This comparative example is basically the same as Example 3, except that an equal mass fraction of water glass is used to replace the modified water glass.

[0094] Comparative Example 2

[0095] This comparative example is basically the same as Example 3, except that the water-binder ratio of the pure slurry A is 0.35; the water-binder ratio of the pure slurry B is 0.20.

[0096] Comparative Example 3

[0097] This comparative example is substantially the same as Example 3, except that, by weight, 1.1 parts of NaOH powder, 25 parts of water and 9 parts of water glass are added at one time and mixed thoroughly to form modified water glass.

[0098] Comparative Example 4

[0099] This comparative example is basically the same as Example 3, except that the modulus of the modified water glass is 1.2.

[0100] The red mud-based aggregates and red mud-based permeable bricks prepared in the above Examples 1-3 and Comparative Examples 1-4 were subjected to TCLP toxicity characteristic leaching test and compressive strength measurement.

[0101] Prepare the extractant: dissolve 5.7 mL of glacial acetic acid in 1 L of pure water and adjust the pH to 2.88 ± 0.05; prepare samples of equal mass: red mud-based aggregate and red mud-based permeable brick;

[0102] The sample was mixed with the leaching agent at a solid-liquid ratio of 1:20, and an automatic constant temperature flip oscillator was used to oscillate at 30±2r / min for 18±2 hours. After standing for 6±0.5 hours, the supernatant was filtered and the heavy metal ion concentration was finally determined by ICP-OES or ICP-MS to determine whether the heavy metal ion concentration of red mud-based aggregates and red mud-based permeable bricks met the national standards and recorded in Table 2.

[0103] Table 2 Heavy metal ion concentrations of As, Cr, Mn and K in red mud-based aggregates and red mud-based permeable bricks

[0104]

[0105]

[0106] According to the relevant data of the above embodiments and comparative examples, it is described as follows:

[0107] The red mud-based aggregates and red mud-based permeable bricks prepared in Examples 1-3 have heavy metal leaching concentrations that meet national standards, and their mechanical properties meet international standards.

[0108] In Comparative Example 1, after replacing the modified water glass with water glass of equal mass fraction, the ordinary water glass has low activity and cannot provide sufficient bonding force, resulting in weakened bonding strength of the internal structure of the slurry A and B, uneven solidification, and defects in the internal structure. As a result, the red mud-based aggregate and red mud-based permeable brick prepared in Comparative Example 1 have internal structural defects, reduced bonding strength, and the heavy metal leaching concentration and mechanical properties do not meet the national standards.

[0109] In Comparative Example 2, the water-binder ratios in both the slurry A and the slurry B were lower than the predetermined range, resulting in poor fluidity of the slurry A and the slurry B. At this time, the solidification time of the slurry A on the substrate surface was accelerated, and a hard shell could not be formed on the substrate surface, resulting in the red mud-based aggregate prepared in Comparative Example 2, and the mechanical properties did not meet the national standards.

[0110] Too little water in the pure slurry B makes it difficult to mix the mineral powder, fly ash and red mud evenly, which limits the production of gelling products such as CSH gel and C(N)-ASH gel, and seriously affects the performance of the pure slurry B. Moreover, when the pure slurry B is mixed with the red mud-based aggregate, the red mud-based permeable bricks prepared in Comparative Example 2 have a local uneven internal structure due to the low fluidity of the pure slurry B, and the leaching concentrations of various heavy metals do not meet the national standards, and the mechanical properties do not meet the national standards.

[0111] In Comparative Example 3, when preparing modified water glass, the order of addition was changed, resulting in uneven reaction of the modified water glass or excessive local concentration, causing the slurry A and slurry B prepared in Comparative Example 4 to be locally too thick or agglomerated, resulting in the mechanical properties of the red mud-based aggregate prepared in Comparative Example 2 not meeting national standards, and the leaching concentrations and mechanical properties of various heavy metals in the red mud-based permeable bricks not meeting national standards.

[0112] In Comparative Example 4, after the modulus of the modified water glass dropped to 1.2, its alkalinity was strong and the silicon content was low, resulting in less gelled products generated by the pure slurry A and pure slurry B, which could not effectively seal and fix the heavy metals, causing them to be released when in contact with water or leaching medium. In addition, when the modulus is low, it will affect the uniformity of the gel structure, increase the internal pores of the material, and lead to reduced mechanical properties, so that the mechanical properties of the red mud-based aggregate and red mud-based permeable brick prepared in Comparative Example 5 do not meet the national standards, and the leaching concentrations of various heavy metals do not meet the national standards.

[0113] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A method for preparing red mud-based aggregate, characterized in that: The following steps are involved: S11, mixing light-burned dolomite, mineral powder, fly ash, red mud and water uniformly, ball-milling and drying to obtain a matrix; S12, uniformly mixing silica fume, magnesium silicate cement and modified water glass to prepare a pure slurry A; S13, spraying water to wet the substrate, pouring the substrate into the slurry A, stirring evenly, the slurry A forms a hard shell on the surface of the substrate, and obtaining red mud-based aggregate after the hard shell is solidified.

2. The method for preparing a red mud-based aggregate according to claim 1, characterized in that: In the S11, 2-5 parts of light-burned dolomite, 2-5 parts of mineral powder, 2-5 parts of fly ash, 10-15 parts of red mud and 1-3 parts of water are added in sequence by weight, mixed evenly, and after mixing, ball-milled at a pressure of 5-6 MPa to form the matrix.

3. The method for preparing a red mud-based aggregate according to claim 1, characterized in that: In the S12, 20-50 parts of silica powder, 20-50 parts of magnesium silicate cement and 5-15 parts of modified water glass are added in sequence by weight, and mixed evenly to form the slurry A.

4. The method for preparing a red mud-based aggregate according to claim 1, characterized in that: The modified water glass comprises 5-15 parts of water glass, 1-2 parts of NaOH powder and 20-30 parts of water; In S12, 1-2 parts of NaOH powder and 20-30 parts of water are added in sequence by weight, and after mixing evenly, 5-15 parts of water glass are added and mixed thoroughly to form the modified water glass; The modulus of the modified water glass is 1.3-1.

7.

5. The method for preparing a red mud-based aggregate according to claim 1, characterized in that: The water-to-binder ratio of the pure slurry A is 0.40-0.

55.

6. The method for preparing a red mud-based aggregate according to claim 1, characterized in that: The particle size of the matrix is ​​1-10 mm, and the thickness of the net slurry A of the red mud-based aggregate is 0.90-1.2 mm.

7. A red mud-based aggregate, characterized in that: The red mud-based aggregate is prepared by the preparation method of any one of claims 1 to 6.

8. A method for preparing red mud-based permeable bricks, characterized in that: The red mud-based aggregate according to claim 7 is applied, comprising the following steps: S21, mixing the mineral powder, fly ash, red mud and modified water glass uniformly to form a pure slurry B; S22, mixing the red mud-based aggregate and the pure slurry B to prepare red mud-based permeable bricks.

9. The method for preparing a red mud-based permeable brick according to claim 8, characterized in that: In S21, 20-50 parts of mineral powder, 10-15 parts of fly ash, 10-20 parts of red mud and 5-15 parts of modified water glass are added in sequence by weight, and mixed evenly to form a pure slurry B; The water-to-binder ratio of the pure slurry B is 0.28-0.

38.

10. A red mud-based permeable brick, characterized in that: The red mud-based aggregate is prepared by the preparation method of any one of claims 8-9.